Efficient direct formic acid electrocatalysis enabled by rare earth-doped platinum-tellurium heterostructures - Xin Lin; Shize Geng; Xianglong Du; Feiteng Wang; Xu Zhang; Fang Xiao; Zhengyi Xiao; Yucheng Wang; Jun Cheng; Zhifeng Zheng; Xiaoqing Huang; Lingzheng Bu (Nature Communications)
Abstract The lack of high-efficiency platinum (Pt)-based nanomaterials remains a formidable and exigent challenge in achieving high formic acid oxidation reaction (FAOR) and membrane electrode assembly (MEA) catalysis for direct formic acid fuel cell (DFAFC) technology. Herein, we report 16 Pt-based heterophase nanotrepang with rare earth (RE)-doped face-centered cubic Pt (fcc-Pt) and trigonal Pt-tellurium (t-PtTe2) configurations ((RE-Pt)-PtTe2 HPNT). Yttrium (Y) is identified as the optimal dopant, existing as single sites and clusters on the surface. The (Y-Pt)-PtTe2 HPNT/C demonstrates the superior mass and specific activities of 6.4 A mgPt −1 and 5.4 mA cm-2, outperforming commercial Pt/C by factors of 49.2 and 25.7, respectively. Additionally, it achieves a normalized MEA power density of 485.9 W gPt −1, tripling that of Pt/C. Density functional theory calculations further reveal that Y doping enhances HCOO* intermediate adsorption and suppresses CO intermediate formation, thereby promoting FAOR kinetics. This work highlights the role of RE metals in heterostructure regulation of Pt-based anodic nanomaterials for achieving the efficient direct formic acid electrocatalysis.